Comparative analysis reveals distinctive genomic features of Taiwan hot-spring cyanobacterium Thermosynechococcus sp. TA-1 - Cheng, Yen-I; Lin, Yu-Chen; Leu, Jyh-Yih; Kuo, Chih-Horng; Chu, Hsiu-An (Frontiers in Microbiology, 2022)
Thermosynechococcus is a genus of thermophilic unicellular cyanobacteria that dominates microbial mats in Asian non-acidic hot springs. These cyanobacteria are the major primary producers in their ecological niches and are promising sources of thermostable enzymes for biotechnology applications. To improve our understanding of these organisms, we conducted whole-genome sequencing of a novel strain for comparative analysis with other representatives in the same genus. This newly characterized strain, Thermosynechococcus sp. TA-1, was isolated from the Taian hot springs in Taiwan. Analyses based on average nucleotide identity (ANI) and genome-scale phylogeny suggested that TA-1 and another Taiwanese strain CL-1 belong to a novel species-level taxon. Two metagenome-assembled genomes (MAGs) originated from India represent the sister group, and Thermosynechococcus elongatus PKUAC-SCTE542 from China is the next closest lineage. All cultivated strains and MAGs from Japan form a separate monophyletic clade and could be classified into two species-level taxa. Intriguingly, although TA-1 and CL-1 share 97.0% ANI, the genome alignment identified at least 16 synteny breakpoints that are mostly associated with transposase genes, which illustrates the dynamic nature of their chromosomal evolution. Gene content comparisons identified multiple features distinct at species- or strain-level among these Thermosynechococcus representatives. Examples include genes involved in bicarbonate transportation, nitric oxide protection, urea utilization, kanamycin resistance, restriction modification system, and chemotaxis. Moreover, we observed insertion of type II inteins in multiple genes of the two Taiwanese strains and inferred putative horizontal transfer of an asparagine synthase gene (asnB) associated with a exopolysaccharides gene cluster. Taken together, while previous work suggested that strains in this genus share a highly conserved genomic core and no clear genetic differentiations could be linked to environmental factors, we found that the overall pattern of gene content divergence is largely congruent with core genome phylogeny. However, it is difficult to distinguish between the roles of phylogenetic relatedness and geographic proximity in shaping the genetic differentiations. In conclusion, knowledge of the genomic differentiation among these strains provides valuable resources for future functional characterization.